The Effect of Accounting on Hajj Savings at Pt Bank Sumut Gunung Tua Branch Office - Fitri Yani Sibarani; Kamila K (Penerbit Jurnal Indonesia, 2022)
This study aims to determine how accounting influences Hajj savings at PT Bank Sumut Kanto, Gunung Tua Branch. The analysis technique used in this article will use a descriptive method with a qualitative approach, namely by collecting and filtering the data obtained from the operational function agency thoroughly and in detail and then described in order to get a clear explanation. Based on the results of data collection at PT Bank Sumut Gunung Tua Branch Office that the management of the accounting system is in accordance with the regulations of the PT Bank Sumut head office.